International R&D an examination on knowledge management practices and innovation intensity in Malaysian MSC cluster - Hasnan, Norlena; Hashim, Fariza; Abu Bakar, Abdul Rahim (Universiti Utara Malaysia, 2011)
Effective knowledge management (KM) has been recognized as one important method to improve performance. Knowledge application and generation absorb in the process of R&D stimulate the creation of innovations. Hence, this study aims to examine the efficiency of knowledge management practices by the international firms located in Multi-media Super Corridor (MSC). This is vital in order to understand further the role of MSC as a support for innovation planning and implementation of the K-economy.The study only confined to the firms established in the MSC area.It is believed that the firms in this area are all R&D firms which are heavily engage in innovation and knowledge management practices.The findings of the study indicate that the KM practices were applied by the firms were part of the knowledge management practices.There were also various associations between the variables of knowledge management practices and innovation.Nevertheless, most of these associations were positive in nature which indicate that the stronger the relationship, greater the knowledge management practices.In addition, the findings reveal that international firms did not extensively engage in the R&D based on their level of innovation.The study is interesting and has various potential to be further explored.It is suggested that the result could be more comprehensive if the study includes all international firms in the whole country. The construct of innovation intensities and other innovative capabilities also can be extended in order to discover more factors contributing to the effectiveness of the knowledge management practices on the international firms’ innovative behavior in Malaysia.